PENGEMBANGAN PEMBELAJARAN PENJAS ADAPTIF MELALUI MEDIA PERMAINAN BANGUN PINTAR BERWARNA PADA SISWA TUNARUNGU SDLB NEGERI SEMARANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the results of the adaptive learning model penjas media through smart wake -colored game at Semarang State SDLB deaf students . The game is a wake -colored smart penjas innovation in adaptive learning that is instructive . This research is a development . The analysis procedure includes product development product that will be created , developed the initial product , expert validation and revision , testing and revision of small groups , large groups and test the final product . The data was collected using a questionnaire derived from the expert evaluations and observations of students . The data analysis technique used is descriptive percentages . From the test data showed that the initial product evaluation , expert penjas 84.0 % ( Good ) , learning experts I 85.2 % ( Good ) and expert learning II 84.0 % ( Good ) small test group 87.55 % ( Good ) and field trials / large group 91.86 % ( Very Good ) . From the available data it can be concluded that the model of an adaptive learning game penjas smart wake of this color can be used for deaf students grade 2 SDLB Semarang.